Spleen tyrosine kinase mediates the γδTCR signaling required for γδT cell commitment and γδT17 differentiation - Muro, Ryunosuke; Narita, Tomoya; Nitta, Takeshi; Takayanagi, Hiroshi (Frontiers in Immunology, 2023)
The γδT cells that produce IL-17 (γδT17 cells) play a key role in various pathophysiologic processes in host defense and homeostasis. The development of γδT cells in the thymus requires γδT cell receptor (γδTCR) signaling mediated by the spleen tyrosine kinase (Syk) family proteins, Syk and Zap70. Here, we show a critical role of Syk in the early phase of γδT cell development using mice deficient for Syk specifically in lymphoid lineage cells (Syk-conditional knockout (cKO) mice). The development of γδT cells in the Syk-cKO mice was arrested at the precursor stage where the expression of Rag genes and αβT-lineage-associated genes were retained, indicating that Syk is required for γδT-cell lineage commitment. Loss of Syk in γδT cells weakened TCR signal-induced phosphorylation of Erk and Akt, which is mandatory for the thymic development of γδT17 cells. Syk-cKO mice exhibited a loss of γδT17 cells in the thymus as well as throughout the body, and thereby are protected from γδT17-dependent psoriasis-like skin inflammation. Collectively, our results indicate that Syk is a key player in the lineage commitment of γδT cells and the priming of γδT17 cell differentiation.